The impact of time factors on overall survival in patients with nasopharyngeal carcinoma: a population-based study - Chen, Po-Chun (Radiat Oncol, 2016)
BACKGROUND: Nasopharyngeal carcinoma (NPC) is most common in Southeast Asia. The purpose of this study is to investigate the correlation between wait time and length of radiotherapy and overall survival (OS) of NPC patients in Taiwan. METHODS: From Taiwan’s National Health Insurance Research Database, this nationwide population-based cohort study identified 3605 NPC patients who received radiotherapy between 2008 and 2011. The impact of time factors on NPC survival rates was estimated with Kaplan-Meier survival curves. A multivariable Cox hazards regression model tested the significance of results after adjustment for other covariables. RESULTS: In all, 317 patients had wait times >4 weeks, 1404 patients had longer duration of radiotherapy (i.e., >10 weeks) and 499 died. Patients with wait times > 4 weeks and length of radiotherapy ≤ 10 weeks didn’t have significantly inferior survival. Patients with wait times >4 weeks and length of radiotherapy >10 weeks had significantly lower OS than other groups, with an adjusted hazard ratio of 1.7 (95 % CI, 1.10–2.60). CONCLUSION: Time was a significant prognostic factor for NPC patients who had both >4 weeks wait times and length of radiotherapy >10 weeks. Patients with wait time > 4 weeks and length of radiotherapy ≤ 10 weeks had a trend toward an inferior survival.